Multitemporal assessment of land-use change in a rapidly urbanizing coastal region in Turkey using remote sensing - Cetin, Mufit; Musaoglu, Nebiye; Tanik, Aysegul (Mary Ann Liebert, Inc, 2008)
Turkey is among the developing countries facing rapid population increase and unplanned growth, especially along the coastal regions in the vicinity of metropolitan cities. In this study, the topographic maps, together with satellite images, were utilized to evaluate the land-use/cover changes that have occurred during the past 30 years in the coastal region of Tuzla-Gebze, located within the metropolitan cities of Istanbul and Kocaeli. The topographic 1:25,000 scaled maps of 1976, satellite images belonging to years 1987, 1997, and 2005 LAND-SAT 5 TM and 2000 LANDSAT 7 ETM+, together with aerial photographs, orthophoto maps, and various thematic maps, were used as effective data sources for classification analysis and interpretation of the change detection results. In the study, percent distribution and areal changes of different land uses between years 1976 and 2005 were calculated from land use classification results. Urban expansion during the term of 1976-1987, 1987-2000, and 2000-2005 was realized as 220%, 55%, and 15%, respectively, according to the classification results. This enlargement mainly occurred in the areas nearer to the highways and the coastline. The decline of barren lands and their conversion to residential areas occurred far from the center of the region prior to 2005. Furthermore, matrix analysis that enables the production of a thematic layer containing a separate class for every coincidence of classes in two layers was also applied to the classified satellite images to provide the land-use changes in detail both visually and numerically. The analyses belonging to years 1976, 1987, 2000, and 2005 put forth the areal changes of water, green area, barren land, and urban area classes determined during the study years that allow the researchers to make detailed investigations.
Keywords: remote sensing; land-use/cover; land classification; matrix analysis; Turkey